Interoperabilidad entre el Repositorio Institucional y servicios en línea en la Universidad Nacional de La Plata - De Giusti, Marisa Raquel (2013)
La Plata National University (UNLP, Universidad Nacional de La Plata) has as priority objective the dissemination of all knowledge generated in the institution, in order to return to the society part of the efforts invested in the public University. To that end, different initiatives have been launched, along with new services as well as research and development projects to foster these services. The Intellectual Creation Dissemination Service (SEDICI, Servicio de Difusión de la Creación Intelectual) is the UNLP Institutional Repository, and holds different classes of scientific and academic materials produced inside the University, including journal articles, conferences' publications, theses, ordinances, books, e-books and audio-documents. This institutional repository, the largest one in Argentina and one of the largest ones in Latin America, possesses a central role in the dissemination of UNLP’s intellectual production and in the coordination with other projects and services such as UNLP’s Journals Portal, supported by OJS, and UNLP’s Conferences Portal, supported by OCS. In this article we explain the different mechanisms implemented from UNLP to ease the interaction between its institutional repository, SEDICI - supported by Dspace - and those portals, to avoid efforts duplication, and to maximize an open and free knowledge dissemination. Such mechanisms include technological developments based on different protocols (such as RSS/Atom, Sword, OAI-PMH) to establish an unified way of communication between systems, and the development of plugins that enable administrators to export information from the different tools in a format that could be understood by other systems. These involve the establishing of workflows among workgroups of the different services too, with the objective of building a unified mechanism that contemplates the methods and tools used to export/import data fomr and to the repository. In addition, other efforts driven from SEDICI as well as the University presidency are also mentioned in this document. These efforts seek to ensure the preservation of all intellectual production while they provide new mechanisms to maximize the visibility of the scientific and academic documents. Other actors and directions from the UNLP are also involved in such efforts, like the Publishing House EDULP, the Distance Education Direction (EAD), and the University Radio.